Modern essentials of architectural, Design and computation principles dictating the lighting of spaces - Ar Deepthi A; Ar Antara Nandy; Utpal Kumar Nandy (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2020)
Happiness brings good health and wellbeing. A properly lit space helps to bring in a sense of happiness. Nowadays, urban people in general rely on artificial lighting mostly even during daytime especially within office buildings. This research paper intents to discuss about responsibilities of a lighting designer, the effect of lighting on emotional well-being of the occupants and attainment of comfort from a lighting designer's point of view. Offices, factories and public gathering spaces such as markets etcetera are given more emphasis in this research. The latest trends include day-lighting methodology, passive lighting, anti-glare lighting and lastly, from good health perspective, anti-bacterial LED lights. Some of the significant psychological aspects discussed include mood betterment caused by artificial lighting, increasing hygiene through lighting and therapeutic effects of lighting. This paper features a few case studies where the scenes and corresponding lux values (using the software Dialux Evo and Dialux 4.13) have been charted along with the commentaries on comfort which have been achieved. Other notable Lighting design software include Autolux, Agi32, Luxicon, Lite Pro and Lumen micro. Also, we intend to discuss basic Lighting Analysis techniques and Photoshop color correction techniques in separate individual sections.